Effectiveness Of Electronic Pediatric Triangle Assesment Flipchart To Nurse Knowledge - Wasilah, Wasilah; Maryani, Maryani; Nuraidah, Nuraidah; Murtiani, Farida (Media Keperawatan Indonesia, 2023)
This study aims to determine the effectiveness of electronic PAT flipchart to the Nurse’s knowledge. The research is Quasi Experiment without control group. The sample was the nurses in the emergency room and the pediatric inpatient room who met inclusion and exclusion criteria.We collected sample using total sampling technique and collected 46 samples. Our study showed that knowledge score before the intervention was 16.37 and most of them had good knowledge, namely 38 (82.6) while after the intervention was 19.22 and most of them had good knowledge, namely 45 (97.8). We proved significant difference in knowledge scores before and after giving the PAT electronic flipchart (Pvalue=0.000).